STEREOTYPICAL BARBIE ARCHETYPAL ROLE IN NAVIGATING THE STORYLINE OF “BARBIE” (2023) BY GRETA GERWIG - Fitriyah, Fitriyah; Anindya, Farah Diva (Elite : English and Literature Journal, 2024)
The Barbie (2023) film has succeeded in presenting more than just a light spectacle about the iconic doll. Behind the bright colors and seemingly perfect atmosphere of Barbie Land, this film explores profound themes, including identity, gender roles, feminism, and social criticism of society’s expectations of women. The archetypal character of Stereotypical Barbie, as the main character, plays a vital role in this film as a representation of the perfect woman in Barbie Land. This study aims to analyze the psychological factors in Barbie’s journey that may interfere with or support her. This is reflected in several patterns called archetypes in her personality traits and behavior when facing several stages of the storyline. The data for this study used the film "Barbie" (2023) by Greta Gerwig. The research method used is qualitative descriptive, using a psychoanalytic approach (Jung’s Archetype theory). The results found seven archetypal characters represented by Stereotypical Barbie. The findings are Persona, Shadow, Animus, The Great Mother, Hero, Trickster, and Self. These findings will help us understand how the psychological layers in Barbie’s story reveal complex dynamics about women’s roles, identity crises, and the search for self.